Literature Review: Synthesis Methods of NiFe2O4 Nanoparticles for Aqueous Battery Applications - Haq, Fatih; Zein, Muhammad; Gabriella, Rachel; Putri, Silmi; Nandiyanto, Asep; Kurniawan, Tedi (Unijourn Publisher, 2021)
Today, the application of NiFe2O4 nanoparticles is increasing in the field of technology that is in great demand, thereby increasing the demand for industrial production. The use of NiFe2O4 nanoparticles can be applied in various technologies, including aqueous batteries. Therefore, an effective method for industrial production is needed. This paper aims to discuss and compare a more efficient method in the synthesis of NiFe2O4. The research method used is a literature review of 62 papers. There are several NiFe2O4 synthesis methods, namely Coprecipitation, Citrate Precursor Technique, Mechanical Alloying, Hydrothermal, Sonochemistry, Reverse Micelle, Sol-Gel, and Pulsed Wire Discharge. The results show that the effective synthesis method of NiFe2O4 is Hydrothermal. This is because the hydrothermal method is economically feasible, environmentally friendly, and has no requirement of high temperatures in the calcination process to produce the final product. The nanoparticle size is around 29.39 nm. This paper is expected to assist in selecting the synthesis method of NiFe2O4.